1
$\begingroup$

I have obtained an integral equation that models a particular physical phenomenon. I wish to convert it into a differential equation so that I can solve it. Here's the equation defined for $z\geq z_0$: \begin{equation} g(z-z_0)=\int_{z_0}^{z}dt~f(t-z_0)g(z-t) \end{equation} After reading post-1 and Fundamental theorem of calculus, I thought this was the answer: \begin{equation} \frac{dg(z-z_0)}{dz}=f(z-z_0)g(0) \end{equation} but obviously this is incorrect, since upon integration again, $g(0)$ will be treated as a constant and so we do not get back the original integral equation. I have also read post-2, post-3, post-4, but still can't figure out the correct way. Any help is appreciated. Thanks in advance.

$\endgroup$
  • 1
    $\begingroup$ I am afraid what you want is not possible since the integral will remain after derivation. Observation: If $z_0 = 0$ and you apply the Laplace transform to your equation, you get $G(s) = F(s)G(s)$, that is $F(s) = 1$ or $G(s) = 0$. $\endgroup$ – Friedrich Philipp Mar 16 '17 at 6:39
2
$\begingroup$

$$g(z-z_0)=\int_{z_0}^{z}f(t-z_0)g(z-t)dt $$

Let $z-t = y$ $$g(z-z_0)=\int_{0}^{z-z_0} f(z-z_0 -y)g(y)dy $$

This implies that for $z-z_0 = t \geq 0$

$$g(t) = (g*f)(t)$$

Then apply Laplace to both sides

$$G(s) = G(s) F(s)$$

I think you can go from here.

$\endgroup$
3
$\begingroup$

As Friedrich Philipp commented.

If you apply the fundamental theorem of calculus $$\begin{equation} g(z-z_0)=\int_{z_0}^{z}~f(t-z_0)\,g(z-t)\,dt \end{equation}$$ $$\begin{equation} \frac{dg(z-z_0)}{dz}= f(z-z_0)\,g(0)+\int_a^z f(t-z_0)\, g'(z-t) \, dt \end{equation}$$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.